Associaton of Retinol Binding Protein 4 (RBP4) Levels With Hyperuricemia: A Cross-Sectional Study in a Chinese Population - Hong, Guo-bao; Shao, Xiao-fei; Li, Jia-min; Zhou, Qin; Ke, Xiao-Su; Gao, Pei-Chun; Li, Xiao-Lin; Ning, Jing; Chen, Hai-Shan; Xiao, Hua; Xiong, Chong-Xiang; Zou, Hequn (Frontiers in Endocrinology, 2022)
Background: There are few studies on predictive biomarkers for hyperuricemia, and the predictive value of these biomarkers tends to be poor. Additionally, no reports have described the predictive value of retinol binding protein 4 (RBP4) for hyperuricemia. Purpose: This study was performed to evaluate the value of RBP4 for predicting the risk of hyperuricemia in a general population, determine whether RBP4 could be used alone or in combination with other factors to predict the risk of hyperuricemia in the general population, and establish an optimum predictive model. Methods: We conducted a population-based cross-sectional survey in 2018, involving a questionnaire, physical examination, and laboratory testing. We enrolled 2303 individuals by stratified random sampling, and 2075 were included in the data analysis after applying the eligibility criteria. Results: Serum RBP4 level had a highly significant association with hyperuricemia (P<0.001). After adjusting for potential confounders, logistic regression indicated that the risk of hyperuricemia was highest in the highest RBP4 quartile (odds ratio: 7.9, 95% confidence interval [CI]: 4.18–14.84, compared to the lowest quartile). The area under the receiver operating characteristic (ROC) curve (AUC) for RBP4 was 0.749 (95% CI: 0.725–0.774, P<0.001), which was higher than that for all the other predictors assessed. The optimum model for predicting hyperuricemia in the general population consisted of RBP4, sex (male), body mass index, serum creatinine, high-sensitivity C-reactive protein, fasting blood glucose, insulin, and alcohol consumption. The AUC was 0.804 (95% CI: 0.782–0.826, P<0.001). Separate predictive models were then established for each sex. Conclusions: RBP4 is strongly associated with hyperuricemia, and its predictive value was higher than that of traditional predictors.